2017
DOI: 10.1177/0023830916687793
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Investigation of the Relationship between Motivation and Late Second Language Speech Learning in Classroom Settings

Abstract: The current study set out to examine the role of learner motivation in second language (L2) speech learning in English-as-a-Foreign-Language classrooms. The motivational orientations of 40 firstyear university Japanese students were surveyed via a tailored questionnaire and linked to their spontaneous speech development, elicited via a timed picture description task at the onset and end of one academic semester, in terms of perceived comprehensibility (i.e., ease of understanding) and accentedness (i.e., lingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 59 publications
(111 reference statements)
1
28
0
Order By: Relevance
“…Although raters receive only minimal training or practice, they tend to show relatively high interrater reliability (Cronbach α > .90), indicating the presence of a shared notion of comprehensibility (Saito, Trofimovich, & Isaacs, ). Extensive research on comprehensibility assessments has suggested that native raters selectively attend to those linguistic features that hinder successful communication or prompt understanding (for a list of communicatively important linguistic features, see Derwing & Munro, ; Saito et al., ; Trofimovich & Isaacs, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although raters receive only minimal training or practice, they tend to show relatively high interrater reliability (Cronbach α > .90), indicating the presence of a shared notion of comprehensibility (Saito, Trofimovich, & Isaacs, ). Extensive research on comprehensibility assessments has suggested that native raters selectively attend to those linguistic features that hinder successful communication or prompt understanding (for a list of communicatively important linguistic features, see Derwing & Munro, ; Saito et al., ; Trofimovich & Isaacs, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…One of these studies, Baker‐Smemoe and Haslam (), longitudinally investigated a total of 31 Chinese EFL learners’ L2 motivation (elicited via a subsection of the Pimsleur Language Learning Aptitude Battery) and their L2 oral proficiency development, finding significant associations between the two. In another study, Saito, Dewaele, and Hanzawa () devised a tailored questionnaire for their target population (40 Japanese EFL university students). The students’ different levels of context‐specific motivation—studying English for their future career development as a vague, long‐term goal in a globalized society, which could be captured through the construct of international posture (Yashima, Zenuk‐Nishide, & Shimizu, )—significantly predicted the longitudinal development of the students’ L2 oral proficiency over one academic term.…”
Section: The Present Studymentioning
confidence: 99%
See 3 more Smart Citations